Monocyte-Derived Signals Activate Human Natural Killer Cells in Response to Leishmania Parasites - Messlinger, Helena; Sebald, Heidi; Heger, Lukas; Dudziak, Diana; Bogdan, Christian; Schleicher, Ulrike (Frontiers in Immunology, 2018)
Activated natural killer (NK) cells release interferon (IFN)-γ, which is crucial for the control of intracellular pathogens such as Leishmania. In contrast to experimental murine leishmaniasis, the human NK cell response to Leishmania is still poorly characterized. Here, we investigated the interaction of human blood NK cells with promastigotes of different Leishmania species (Leishmania major, Leishmania mexicana, Leishmania infantum, and Leishmania donovani). When peripheral blood mononuclear cells or purified NK cells and monocytes (all derived from healthy blood donors from Germany without a history of leishmaniasis) were exposed to promastigotes, NK cells showed increased surface expression of the activation marker CD69. The extent of this effect varied depending on the Leishmania species; differences between dermotropic and viscerotropic L. infantum strains were not observed. Upregulation of CD69 required direct contact between monocytes and Leishmania and was partly inhibitable by anti-interleukin (IL)-18. Unexpectedly, IL-18 was undetectable in most of the supernatants (SNs) of monocyte/parasite cocultures. Confocal fluorescence microscopy of non-permeabilized cells revealed that Leishmania-infected monocytes trans-presented IL-18 to NK cells. Native, but not heat-treated SNs of monocyte/Leishmania cocultures also induced CD69 on NK cells, indicating the involvement of a soluble heat-labile factor other than IL-18. A role for the NK cell-activating cytokines IL-1β, IL-2, IL-12, IL-15, IL-21, and IFN-α/β was excluded. The increase of CD69 was not paralleled by NK cell IFN-γ production or enhanced cytotoxicity. However, prior exposure of NK cells to Leishmania parasites synergistically increased their IFN-γ release in response to IL-12, which was dependent on endogenous IL-18. CD1c+ dendritic cells were identified as possible source of Leishmania-induced IL-12. Finally, we observed that direct contact between Leishmania and NK cells reduced the expression of CD56 mRNA and protein on NK cells. We conclude that Leishmania activate NK cells via trans-presentation of IL-18 by monocytes and by a monocyte-derived soluble factor. IL-12 is needed to elicit the IFN-γ-response of NK cells, which is likely to be an important component of the innate control of the parasite.